Influence of large-scale atmospheric circulation and Mediterranean sea surface temperature to extreme land precipitation: the case of storm Alex - Laurent Terray; Margot Bador (Environmental Research: Climate)
Extreme (greater than 500 mm) amount of rain fell in southeastern France and northern Italy on 2nd and 3rd October 2020 during a ‘Mediterranean episode’ triggered by the powerful extratropical cyclone Alex. Here we use a dynamical adjustment methodology based on constructed analogues to assess the contributions of different drivers to the magnitude of this extreme precipitation event. We first show that the mean effect of the observed atmospheric circulation pattern, an intense low-pressure system centered over the coasts of Western Europe associated with a cold pool and a secondary low-pressure system, can explain about 80% of the precipitation event magnitude. By contrasting the effect of Alex atmospheric circulation with an anomalously warm Mediterranean sea and eastern Atlantic ocean versus neutral sea surface temperature (SST) conditions, we show that the influence of September 2020 positive SST anomalies can explain a large fraction of the 20% residual precipitation over southeastern France and northern Italy. Finally, based on a storyline approach, we find that the dynamic component, the atmospheric circulation contribution to the extreme precipitation event, was more extreme than it would have been, had it occurred during the mid-20th century. The increase in the magnitude of the dynamic component since 1950 follows a Clausius–Clapeyron scaling, in agreement with previous studies about the intensity changes of Mediterranean extreme precipitation episodes. (limit = 300 words).